Comprehensive Supramolecular Chemistry II : Facet Control in Nanocrystal Growth - Rao, Ashit; Cölfen, Helmut (My University, 2017)
Morphology is a critical aspect determining the physical behavior of crystals especially at small-length scales. Insights into the fundamental aspects of nucleation and particle growth enable tuning of crystals with respect to shape, size, crystallography, and composition. With a brief introduction on recent developments concerning nucleation and crystal growth, this article presents diverse methods for nanoparticle synthesis and highlights the individual roles of additives, solvents, templates, surfactants, and seeds. Each route is exemplified with interesting examples that facilitate a lucid understanding of underlying methods.
Keywords: Additives; Bioinspired; Crystallization; Crystals; Ions; Kinetics; Monolayer; Morphology; Nanotechnology; Nonclassical; Nucleation; Polymers; Seed overgrowth; Templates; Thermodynamics; 540